Productive Waqf Model as an Alternative for Village-Owned Enterprises Business (BUMDs) Expansion - Achmad Fadlil Abidillah (EKONOMIKA SYARIAH : Journal of Economic Studies, 2021)
This paper aims to create a scientific framework of productive waqf as an alternative financing of business expansions for BUMDes (Badan Usaha Milik Desa). The design of this research is a literature study on theories related to waqf, productive waqf, and rural development. This study finds literacy facts that waqf is a financial source commonly used by Islamic governments in the past. Then, this paper details a concept of productive waqf as an financing alternative to BUMDes’s business expansion, and a systematic model can be formed, which may be a consideration for government policies regarding BUMDes governance, and it is hoped that the application of these findings can provide great benefits for people in rural areas. This finding is expected to be a reference in the framework of scientific thinking in realizing productive waqf as an alternative financing for business expansion from BUMDes and can provide expansive benefits for people in rural areas. Penelitian ini bertujuan untuk membuat suatu kerangka ilmiah konsep wakaf produktif sebagai alternatif pembiayaan ekspansi usaha dari BUMDes. Desain penelitian ini adalah studi kepustakaan mengenai teori-teori yang terkait dengan wakaf, wakaf produktif, serta pembangunan pedesaan. Penelitian ini menemukan fakta literasi bahwa wakaf merupakan sumber finansial yang lazim digunakan oleh pemerintahan Islam di masa silam. Oleh karena itu, penelitian ini kemudian memperinci konsep wakaf produktif sebagai alternatif pembiayaan BUMDes, hingga terbentuk suatu model yang sitematis, bisa menjadi pertimbangan kebijakan pemerintah mengenai tata kelola BUMDes. Sehingga model wakaf produktif dapat menjadi pengembangan terhadap jenis usaha yang dijalankan oleh Badan Usaha Milik Desa, dengan berpatokan kepada tujuan dan prinsip wakaf produktif. Temuan Penelitian ini diharapkan dapat menjadi acuan dalam kerangka berpikir ilmiah dalam mewujudkan wakaf produktif sebagai alternatif pembiayaan ekspansi usaha dari BUMDes dan dapat memberikan manfaat yang besar bagi masyarakat di pedesaan.